Faktor-Faktor Yang Berhubungan Dengan Tingkat Kecemasan Menjelang Persalinan Pada Ibu Primigravida Trimester III di PMB CH Mala Palembang - Veradilla; Mauluddina, Faulia; Suryanti, Yuli; Meriaya Sari, Lely (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Birth planning and readiness to overcome complications is called Birth Preparedness and Complication Readiness is a way to motivate pregnant women and their families to prepare themselves and plan for childbirth in case of an emergency. The purpose of this study was to determine the factors associated with the level of anxiety before childbirth in primigravida mothers in the third trimester. The design of this study was pre-experiment, one group pretest-posttest design approach. The population of this study was all primigravida pregnant women in the third trimester who underwent pregnancy check-ups with a sample of 30 respondents. Data analysis used univariate analysis and bivariate analysis using the Chi square test. The results of the study showed a relationship between education factors (p value = 0.015), age had no relationship (p value = 0.511) and knowledge had a relationship (p value = 0.018) with the level of anxiety in third trimester primigravida at CH Mala PMB in 2022. It is hoped that it can increase counseling on the level of anxiety in third trimester primigravida mothers and provide direct counseling to the community so that local residents' knowledge can increase.